Psychological skills training to support diabetes self-management: Qualitative assessment of nurses' experiences. Issue 5 (October 2016) - Graves, Helen; Garrett, Christopher; Amiel, Stephanie A.; Ismail, Khalida; Winkley, Kirsty
Highlights: Training nurses in psychological skills can have a positive impact on patient care. Nurses require appropriate support from their practice in order to use skills effectively. Qualitative evaluation of psychological skills training can reveal important mechanisms that may contribute to translation into practice. Abstract: Aim: Evidence for the efficacy of psychological skills training as a method of supporting patients' self-management is growing, but there is a shortage of mental health providers with specialist diabetes knowledge to deliver them. Primary care nurses are now increasingly expected to learn and use these techniques. This study explores nurse experience of training in six psychological skills to support patients' self-management of type 2 diabetes. Methods: Semi-structured interviews elicited themes relating to nurses' experiences of participating in a trial of a psychological intervention, the Diabetes-6 study (D-6). Nurses were employed in GP surgeries in 5 South London boroughs. Thematic framework analysis was used to compare and contrast themes across participants. Nine nurses delivering the intervention ( n = 11), and 7 from the control intervention ( n = 12, no psychological element) were interviewed. Results: Three key themes were identified: (i) positive and negative impact of D6 on nurses' practice: positives included patient empowerment; negatives included patients' capacity to engage; (ii) professional boundaries including concerns about over-stepping role as a nurse and (iii) concerns about degree of support from physicians at participating practices in integrating psychological and diabetes care. Conclusion: Primary care nurses report that psychological skills training can have a positive impact on patient care. Significant role adjustment is required, which may be aided by additional support from the practice team. Qualitative evaluation of effectiveness of psychological interventions may reveal processes that hinder or contribute to efficacy and translation. Appropriate support is necessary for primary care nurses to deliver psychological therapies with confidence.